TDP-43 and PINK1 mediate CHCHD10S59L mutation-induced defects in Drosophila and in vitro. - Baek, M.; Choe, Y.J.; Bannwarth, S.; Kim, J.; Maitra, S.; Dorn, G.W.; Taylor, J.P.; Paquis-Flucklinger, V.; Kim, N.C. (Nature communications, 2021)
Mutations in coiled-coil-helix-coiled-coil-helix domain containing 10 (CHCHD10) can cause amyotrophic lateral sclerosis and frontotemporal dementia (ALS-FTD). However, the underlying mechanisms are unclear. Here, we generate CHCH10S59L-mutant Drosophila melanogaster and HeLa cell lines to model CHCHD10-associated ALS-FTD. The CHCHD10S59L mutation results in cell toxicity in several tissues and mitochondrial defects. CHCHD10S59L independently affects the TDP-43 and PINK1 pathways. CHCHD10S59L expression increases TDP-43 insolubility and mitochondrial translocation. Blocking TDP-43 mitochondrial translocation with a peptide inhibitor reduced CHCHD10S59L-mediated toxicity. While genetic and pharmacological modulation of PINK1 expression and activity of its substrates rescues and mitigates the CHCHD10S59L-induced phenotypes and mitochondrial defects, respectively, in both Drosophila and HeLa cells. Our findings suggest that CHCHD10S59L-induced TDP-43 mitochondrial translocation and chronic activation of PINK1-mediated pathways result in dominant toxicity, providing a mechanistic insight into the CHCHD10 mutations associated with ALS-FTD.